Inflation and prices of agricultural products - Nikola Njegovan; Mirela Tomaš Simin (Economic Themes, 2020)
The stability of business in an economy has always been the primary goal that is difficult to achieve, and inflation is most often used as its basic indicator. It is a signal of change in the general price level. The paper analyzes inflation and prices of agricultural and food products as a combined phenomenon, examines their causes and consequences in the Republic of Serbia. Particular importance is attached to the change in prices of agri-food products and the prices of inputs caused by the changes that are taking place at the global level, which are gaining increasing influence in the national context. The change in price parity and the influence of the world monopolistic structure on inflation are pointed out. It also points to the importance of demand, which causes inflation in less developed countries, and which results in higher food prices, additionally putting pressure on wage growth, which, as a rule, is not a consequence of productivity growth. The authors state that with the internationalization of business activities, there was a transfer of influence of international trends on the level and effects of inflation at the national level. Given the trends in the world market, it can be concluded that the prices of agri-food products will not decrease. However, they will - due to the pressure exerted by the constant growth of the population, i.e. on the demand side, demand inflation will constantly manifest.
Keywords: E00; E31; 330; inflation; prices; agricultural products; global perspective